2016
DOI: 10.1039/c5cc10316a
|View full text |Cite
|
Sign up to set email alerts
|

A quinone mediator drives oxidations catalysed by alcohol dehydrogenase-containing cell lysates

Abstract: Spontaneous electron transport to molecular oxygen led to regeneration of oxidised nicotinamide cofactor in cell lysates that contain an alcohol dehydrogenase, a quinone reductase and a quinone mediator. This concept allows the efficient oxidation of alcohols in the presence of alcohol dehydrogenase-containing E. coli lysates and catalytic amounts of the quinone lawsone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…For this purpose, NAD(P)H‐dependent NfsB (oxygen‐insensitive nitroreductase) of Escherichia coli strain K‐12 was used . NfsB has previously been applied to NADP + regeneration by using the concept of redox cycling for the oxidation of alcohols to ketones by alcohol dehydrogenase . Therefore, the synthesized NfsB gene was cloned into the pET19b vector and expressed in E. coli strain BL21.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, NAD(P)H‐dependent NfsB (oxygen‐insensitive nitroreductase) of Escherichia coli strain K‐12 was used . NfsB has previously been applied to NADP + regeneration by using the concept of redox cycling for the oxidation of alcohols to ketones by alcohol dehydrogenase . Therefore, the synthesized NfsB gene was cloned into the pET19b vector and expressed in E. coli strain BL21.…”
Section: Resultsmentioning
confidence: 99%
“…Spontaneous autoxidation of 32 by molecular oxygen from ambient air (see Scheme 7) suggested that quinones, due to their redox properties, may interfere with enzymes involved in maintaining the NAD(P) + /NAD(P)H ratio both in eukaryotic and prokaryotic cells. 54 This led us to apply spontaneous reoxidation of the hydroquinones formed by cellular NAD(P)H-dependent quinone reductases as a source of continuous supply of NAD(P) + . The redox system of lawsone ( 30) and E. coli cell lysate was successfully utilized to oxidize primary and secondary alcohols to the corresponding carbonyl compounds by an NAD(P) + -dependent alcohol dehydrogenase (ADH) (Scheme 12).…”
Section: Nadp + Regeneration Using Lawsone As Mediatormentioning
confidence: 99%
“…Recently, its bactericidal, fungicidal, antimalarial and cytostatic properties were reported 35 . More importantly, its role as a redox mediator was elucidated in many works 6, 7 . As a result, its application field was greatly extended to the pharmaceutical, chemical and other industries 811 .…”
Section: Introductionmentioning
confidence: 99%